Constitutive Equations and Processing Maps for 49MnVS3 Non-Quenched and Tempered Steel - Chen, Y.F.; Peng, X.D.; Xu, H.B.; Jiang, H.D.; Guan, G.H. (Проблемы прочности, 2014)
Flow stress variations of 49MnVS3 non-quenched
and tempered steel are studied in isothermal compression
tests on a Gleeble-1500D thermal simulated
test machine at a deformation temperatures
of 950, 1000, 1150, and 1200° C, and strain rates
of 0.1, 1, 5, and 10 s⁻¹, with obtaining the strain
hardening exponent n and deformation activation
energy Q of the alloy. Thus, the constitutive
equations and processing maps of compression
flow behavior for 49MnVS3 non-quenched and
tempered steel at high temperatures are established.
It shows that the peak stress is shownto
significantly reduced with a decrease in the
strain rate and increase in deformation temperature
when the alloy deforms at high temperature,
and the deformation activation energy is
350.98 kJ/mol. When the true strain of
49MnVS3 non-quenched and microalloyed steel
high-temperature deformation is 0.5, the optimum
process parameters of the alloy are determined
to be 1150–1200° C for the deformation
temperature and 2–10 s⁻¹ for the strain rate,
based on the criterion that the process parameters
of higher power dissipation efficiency values
should be chosen in the dynamic
recrystallization region as the best processing
technology. Изменение напряжения течения незакаленной и закаленной стали 49MnVS3 исследовали путем проведения испытаний на изотермическое сжатие на установке Gleeble-1500D, моделирующей высокотемпературные условия, при температурах деформации 950, 1000, 1150, 1200° C и скоростях деформации 0,1; 1; 5 и 10 c⁻¹ с показателем степени деформационного упрочнения n и значением энергии активации деформации сплава Q. Установлены определяющие уравнения и схемы обработки компрессионного режима течения для незакаленной и закаленной стали 49MnVS3 при высокой температуре. Анализ уравнений показал, что максимальное значение напряжения значительно уменьшается при снижении скорости деформации и повышении температуры деформации, если сплав подвергается деформации при высокой температуре, а значение энергии активации деформации составляет 350,98 кДж/моль. Если значения истинной деформации незакаленной стали 49MnVS3 и высокотемпературной деформации микролегированной стали составляют 0,5, то оптимальные параметры процесса обработки сплава определяются при температуре деформирования 1150…1200° C и скорости деформации 2…10 c⁻¹ на основе критерия, который способствует отбору параметров с более высокой эффективностью рассеивания мощности в области динамической рекристаллизации в качестве оптимальной технологии обработки. Зміну напруження течії незагартованої і загартованої сталі 49MnVS3 досліджували шляхом проведення випробувань на ізотермічний стиск на установці Gleeble-1500D, що моделює високотемпературні умови, за температур деформації 950, 1000, 1150, 1200° C та швидкості деформації 0,1; 1; 5 і 10 c⁻¹ із показником степеня деформаційного зміцнення n і значенням енергії активації деформації сплаву Q. Установлено визначальні рівняння і схеми обробки компресійного режиму течії для незагартованої і загартованої сталі 49MnVS3 за високої температури. Аналіз рівнянь показав, що максимальне значення напруження значно зменшується зі зниженням швидкості деформації і підвищенні температури деформації, якщо сплав зазнає деформації за високої температури, а значення енергії активації деформації дорівнює 350,98 кДж/моль. Якщо значення істинної деформації незагартованої сталі 49MnVS3 і високотемпературної деформації мікролегованої сталі дорівнюють 0,5, то оптимальні параметри процесу обробки сплаву визначаються за температури деформування 1150...1200° C і швидкості деформації 2...10 c⁻¹ на основі критерію, який сприяє відбору параметрів із більш високою ефективністю розсіяння потужності в області динамічної рекристалізації як оптимальної технології обробки.